Determination of the Maximum Roller Bearing Load with Regards to Durability Thereof Using FEM Analysis - Hrcek, Slavomir; Kohar, Robert; Medvecky, Stefan (Communications - Scientific letters of the University of Zilina, 2012)
This paper deals with accurate geometric models of rolling bearing components in the CAD system. This model is then employed to create a static structural analysis used to determine the size of stress between the components of a rolling bearing. Following the stress analysis, we specify the maximum load of a rolling bearing with regards to durability thereof.